Cross-layer routing and time synchronisation in wireless sensor networks. (1st September 2011) - Fedor, Szymon; Collier, Martin; Sreenan, Cormac J.
A common time reference across nodes is required in most Wireless Sensor Networks (WSNs) applications. Also many routing protocols require that nodes communicate according to some predefined schedule for reasons of energy efficiency. However, independent distribution of the time information, without considering the routing algorithm schedule or network topology, may lead to a failure of the synchronisation protocol. This can be avoided by integrating the synchronisation service into the network layer with a so-called cross-layer approach. We present two novel cross-layer routing algorithms, CLEAR and RISS. We implemented and tested the performance of these solutions in simulations and also deployed these routing techniques on sensor nodes using TinyOS. All proposed schemes extend the network lifetime and due to their lightweight architecture they are very efficient on WSN nodes with constrained resources. Hence, it is recommended that a cross-layer approach should be a feature of any routing algorithm for WSNs.